Twin reversed arterial perfusion syndrome (TRAP or acardiac twin) in pregnancy: a case report - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Luh Made Diah Mas Cahyani Putri; Ni Wayan Dewi Purwanti; Made Diah Vendita Sakuntari; Ni Putu Nining Gianni; Ni Komang Anik Pirgantari; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: A type of pregnancy that occurs in monochorionic twin pregnancies which results in the coexistence of normal